IMPLEMENTATION OF ART THERAPY TO REDUCE ANXIETY IN NEW STUDENTS IN ELEMENTARY SCHOOL : A SYSTEMATIC LITERATURE REVIEW - Hafida Fifi Anggraini (Universitas Pendidikan Indonesia, 2022)
Education is one of the important aspects that must be carried out by every human being from an early age. However, in the education process, there are so many obstacles that will be passed by a person, one of which is anxiety. The method used in this research is qualitative. The method used in this study consists of two stages, namely the data collection stage and the data analysis stage. The conclusion is that elementary school children who have just entered school experience anxiety because of several things such as not knowing or fearing plunging into a new environment, bad experiences that have occurred in the past, and excessive fear of an object or person, one of them namely the existence of teachers. Art Therapy is a solution to overcome excessive anxiety experienced by students.